Pathways for glycoprotein degradation in mammalian cells - Kukushkin, N; Nikolay Kukushkin (2011)
In mammalian cells, N-glycoproteins comprise the bulk of secretory cargo. N-glycosylation is tightly linked to the mechanisms of co- and post-translational folding and quality control in the endoplasmic reticulum (ER). Aberrant glycoproteins must be cleared from the secretory pathway. Several mechanisms for glycoprotein degradation exist, of which ER-associated degradation (ERAD) is most well-studied. The latter involves retrotranslocation of misfolded glycoproteins into the cytosol, followed by proteasomal destruction of the polypeptide. N-linked oligosaccharides are removed from glycoproteins during degradation to form free oligosaccharides (FOS). FOS analysis has been employed to gain a global, rather than single protein-centred view of the pathways of ERAD and the mechanisms of its regulation. It was established that convergent ERAD pathways, distinct in the site of deglycosylation, as well as sensitivity to a number of modulators, exist in the cell. It was further demonstrated that the pathway leading to the production of ER-localised FOS is linked to retrograde Golgi-to-ER transport and is masked by the activity of Golgi endomannosidase. Investigating the involvement on the latter in ERAD has uncovered an endomannosidase-mediated pre-degradative glycoprotein processing route and showed that endomannosidase can rescue a fraction of glycoproteins from degradation following inhibition of ER glucosidases. Further investigation of endomannosidase activity and specificity in different cell lines showed that the ability of the enzyme to process truncated monoglucosylated oligosaccharides appears to be necessary and sufficient for evolutionary conservation in mammals. Overall, the data presented have demonstrated on the global level the connections between the pathways for glycoprotein degradation and processing in the Golgi apparatus, underlining the complexity of biosynthetic regulation in the secretory pathway.